Acquisition of Phonological Competence in Five-Year-Old Mentally Disabled Children - Octaria Putri Nurharyani; Bivit Anggoro Prasetyo; Nila Mega Marahayu; Shofi Mahmudah Budi Utami; Widya Putri Ryolita (Faculty of Humanities, Universitas Jenderal Soedirman, 2022)
This research aims at describing language acquisition particularly at the level of phonological competence attained by mentally retarded children. The data in this research are gathered from children, who is mentally retarded, at the Panti Asuhan Yatim Sejahtera Banjarnegara. These data include vocabularies which are primarily nouns, for instance the name of transportations, fruits, and buildings. This is a descriptive-qualitative research of which steps were giving stimuli to the targeted child to pronounce some vocabularies. These pronounced-vocabularies were then employed in this research to further be examined. In order to discover the stages of language acquisition specifically at the level of phonological competence, the data will be analyzed with phonetic syllabus. Based on the result of the analysis, it indicates that the language acquisition of this mentally disabled child phonologically pronounced vocoid [i], [I], [e], [«], [a], [u], [U], [o], [¿], and [\]; and contoid sounds [p], [b], [t], [d], [k], [g], [c], [j], [h], [l], [m], [n], [÷], [w]; while sounds such as [Ö], [s], [r], [z], [q], and [v] were not able to be pronounced. In short, the phonological stage of language acquisition by mentally disabled child was obtained but it was not fully acquired.This research aims at describing language acquisition particularly at the level of phonological competence attained by mentally retarded children. The data in this research are gathered from children, who is mentally retarded, at the Panti Asuhan Yatim Sejahtera Banjarnegara. These data include vocabularies which are primarily nouns, for instance the name of transportations, fruits, and buildings. This is a descriptive-qualitative research of which steps were giving stimuli to the targeted child to pronounce some vocabularies. These pronounced-vocabularies were then employed in this research to further be examined. In order to discover the stages of language acquisition specifically at the level of phonological competence, the data will be analyzed with phonetic syllabus. Based on the result of the analysis, it indicates that the language acquisition of this mentally disabled child phonologically pronounced vocoid [i], [I], [e], [«], [a], [u], [U], [o], [¿], and [\]; and contoid sounds [p], [b], [t], [d], [k], [g], [c], [j], [h], [l], [m], [n], [÷], [w]; while sounds such as [Ö], [s], [r], [z], [q], and [v] were not able to be pronounced. In short, the phonological stage of language acquisition by mentally disabled child was obtained but it was not fully acquired.